Recent Advances in Chemical Biology of Mitochondria Targeting - Wang, Haiwei; Fang, Bin; Peng, Bo; Wang, Limin; Xue, Yufei; Bai, Hua; Lu, Shenci; Voelcker, Nicolas H.; Li, Lin; Fu, Li; Huang, Wei (Frontiers in Chemistry, 2021)
Mitochondria are vital subcellular organelles that generate most cellular chemical energy, regulate cell metabolism and maintain cell function. Mitochondrial dysfunction is directly linked to numerous diseases including neurodegenerative disorders, diabetes, thyroid squamous disease, cancer and septicemia. Thus, the design of specific mitochondria-targeting molecules and the realization of real-time acquisition of mitochondrial activity are powerful tools in the study and treatment of mitochondria dysfunction in related diseases. Recent advances in mitochondria-targeting agents have led to several important mitochondria chemical probes that offer the opportunity for higher selective targeting molecules, novel biological applications and therapeutic strategies. This review details the structural and physiological functional characteristics of mitochondria, and comprehensively summarizes and classifies mitochondria-targeting agents. In addition, their pros and cons and their related chemical biological applications are discussed. Finally, the potential biomedical applications of these agents are briefly prospected.